Parents’ acceptance of human papilloma virus vaccination for their daughters in adet town, North Gojjam zone, Northwest Ethiopia: A mixed method study - Bezawit kassa; Asiya Mohammed; Gizachew Tadesse Wassie (PLoS ONE, 2025)
Human papilloma virus vaccination is an effective way to reduce cervical cancer. Although the health of adolescents is the priority goal across the globe, including Ethiopia, parent s’ acceptance of Human papilloma virus vaccination for their daughters becomes a big challenge in Ethiopia. This study aimed to assess parent’s acceptance of human papilloma virus vaccination for their daughters and associated factors in Adet town, northwest Ethiopia, 2024. Community based mixed method study was employed from May 24 to June 27, 2024. For quantitative data, the sample size was 319 and systematic random sampling technique was used to select study participants. Structured questionnaires were administered for quantitative data, and interview guides were used for qualitative data. The quantitative data was coded, entered and cleaned using Epi info software and exported to SPSS version 25 for analysis. Descriptive statistics, bivariable and multivariable logistic regression analysis were used. Variables with p-value of <0.05 with 95% confidence interval and adjusted odds ratio in multivariable analysis were considered as statistically significant factor for the outcome variable. Thematic analysis approached was employed to analyse qualitative data. Results were presented in tables, texts, charts and graphs. In this study, 249(78.1%) with 95%CI: 73.0–82.4) of parents accept HPV vaccination for their daughters. Knowledge (AOR = 2.96, 95% CI: 1.43–6.10), attitude (AOR = 3.47, 95%CI: 1.71–7.04), subjective norms (AOR = 3.20, 95% CI: 1.56–6.51) and safety concern (AOR = 8.20, 95%CI: 3.45–19.49) were significantly associated factors with parents’ acceptance of HPV vaccine. Qualitative results identified barriers to parental acceptance of the HPV vaccine for daughters, including fear of side effects like infertility, perceiving it as contraceptive method, lack of HPV knowledge, and absence of institutional accountability. Facilitators included influential stakeholder engagement, positive perceptions of the vaccine’s benefits, and confidence in its safety and efficacy. The result of this study seems promising as a more than two thirds of women accept to vaccinate their daughters against HPV though there are still misconceptions, safety and efficacy concerns. To foster cervical cancer prevention efforts, parents’ health education should address vaccination safety concerns, improve HPV knowledge, and foster positive attitudes towards vaccinating daughters.